2022
DOI: 10.1002/jbt.23203
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate (EGCG) attenuates inflammatory responses and oxidative stress in lipopolysaccharide (LPS)‐induced endometritis via silent information regulator transcript‐1 (SIRT1)/nucleotide oligomerization domain (NOD)‐like receptor pyrin domain‐containing 3 (NLRP3) pathway

Abstract: The protective effects of epigallocatechin‐3‐gallate (EGCG) on lipopolysaccharide (LPS)‐induced endometritis in vivo and in vitro will be explored in this study. The endometritis model was induced in female BALB/c mice uterus by perfusion with lipopolysaccharide (LPS) and EGCG were administered at 1 h before LPS induction. The primary bovine endometrial epithelial cells (BEECs) were treated with EGCG for 1 h before LPS stimulation. Uterine histopathological changes, myeloperoxidase (MPO) activity, inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…An experimental study illustrated that dioscin attenuates the severity of subarachnoid hemorrhage through inhibition of NLRP3 inflammasome via a SIRT1-dependent pathway. Different studies revealed that SIRT1 has a protective effect against neurodegeneration and neuronal injury (Di et al 2022 ). SIRT1 activation by resveratrol leads to a protective effect against complications in cerebral ischemia.…”
Section: Mechanistic Role Of Sirt1 In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study illustrated that dioscin attenuates the severity of subarachnoid hemorrhage through inhibition of NLRP3 inflammasome via a SIRT1-dependent pathway. Different studies revealed that SIRT1 has a protective effect against neurodegeneration and neuronal injury (Di et al 2022 ). SIRT1 activation by resveratrol leads to a protective effect against complications in cerebral ischemia.…”
Section: Mechanistic Role Of Sirt1 In Pdmentioning
confidence: 99%
“…SIRT1 can reduce cerebral vasospasm via modulation of the expression and activation of NLRP3 inflammasome as well as regulation of eNOS. As well, SIRT1 activation promotes ischemic tolerance by increasing HIF-1 through the SIRT1-dependent pathway (Di et al 2022 ). These findings proposed that SIRT1 activation represents a promising strategy to reduce ischemic brain injury.…”
Section: Mechanistic Role Of Sirt1 In Pdmentioning
confidence: 99%
“…To date, PFDA is known to activate the NLRP3 inflammasome. In recent years, EGCG has been found to inhibit NLRP3 inflammasome-related inflammatory responses and organ damage in various animal models [49][50][51][52], and these findings revealed that EGCG is an effective natural ingredient for targeting NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 95%
“…One study showed that epigallocatechin-3gallate suppressed NLRP3 inflammasome activation. 39 Another study reported that epigallocatechin-3-gallate improved NLRP3 inflammasome activation in diabetic rats' kidneys. 40 We found docking scores of NLRP3 NACHT domain ADP and inhibitor binding sites with (-)-epicatechin as 8.8 and 8.1 respectively.…”
Section: Binding Free Energymentioning
confidence: 99%